Pulsed electric field processing of edible insect slurries induces thermally-assisted microbial inactivation - L.J.H. Sweers; M. Mishyna; L.M. Ahrné; R.M. Boom; V. Fogliano; T. Patra; C.M.M. Lakemond; J.K. Keppler (Current Research in Food Science)
Insect-based food ingredients are emerging as sustainable protein sources, but their production requires ensuring microbial safety and inactivation of endogenous enzymes to avoid undesirable proteolysis, without compromising protein structure. While traditional thermal processing affects the protein structure, the potential of pulsed electric field (PEF) technology to inactivate microorganisms in lesser mealworm and house cricket slurries at pH 3 while simultaneously retaining the native protein structure is yet unexplored.Lesser mealworm and house cricket slurries at pH 3 were subjected to continuous and batch PEF treatments with varying intensities (0–450 kJ/kg). Microbial inactivation (aerobes, anaerobes, yeasts, and moulds), temperature changes, protein solubility, protein structure (SDS-PAGE and FTIR), and endogenous protease activity were assessed.For both insect species, high-intensity PEF (>150 kJ/kg) achieved up to 5 log microbial reduction, but increased temperatures up to 75 °C, altering protein structure. Low-intensity PEF did not affect protein conformation and protease activity, but was not effective in microbial inactivation (<1 log reduction).We conclude that while PEF can effectively inactivate microorganisms, it cannot be considered a non-thermal method for the present sample conditions due to the temperature increase at higher intensities. PEF could be well-suitable for incorporation in hurdle techniques, such as combinations with moderate heating. Future research should investigate synergistic effects of PEF, also for using alternative PEF set-ups, with other mild processing techniques for effective microbial inactivation while preserving native protein structure. Furthermore, optimal PEF intensities for enhanced protein solubility should be explored.